Characteristics of Patient Waiting Times at Puskesmas Kanjilo - Istiqamah, Nurul Fajriah; Dahlan, Nur Alam (Science Tech Group, 2026)
Patient waiting time is widely recognized as a key performance indicator of primary healthcare service quality, reflecting operational efficiency and accessibility of care. Despite national regulations in Indonesia requiring outpatient waiting times to be under 60 minutes, compliance remains inconsistent across primary healthcare facilities. This study aimed to examine the characteristics of outpatient waiting times at Kanjilo Primary Health Center, Gowa Regency, in 2025. A quantitative descriptive study was conducted involving 297 adult outpatients selected through simple random sampling from a total population of 1,141 visitors in April 2025. Data were collected using a validated and reliable structured questionnaire and analyzed using univariate statistical methods. The findings revealed that 70.7% of patients experienced waiting times of 60 minutes or longer, while only 29.3% received services within the recommended standard. The patient population was predominantly female (76.1%) and largely composed of housewives (55.6%). These results indicate persistent inefficiencies in outpatient service delivery, particularly during peak service hours, compounded by administrative delays and limited service capacity. The study highlights the need for structural and managerial interventions, including improved queue systems, optimized staff allocation, and enhanced administrative processes, to reduce waiting times and improve the overall performance of primary healthcare services.